2014
DOI: 10.1186/1471-2261-14-150
|View full text |Cite
|
Sign up to set email alerts
|

I(f) current channel inhibitor (ivabradine) deserves cardioprotective effect via down-regulating the expression of matrix metalloproteinase (MMP)-2 and attenuating apoptosis in diabetic mice

Abstract: BackgroundIvabradine (IVBD), a novel I(f)-channel inhibitor and specific heart rate-lowering agent, is known to have anti-oxidative activity that promotes endothelial function. However, the molecular mechanism through which IVBD acts on cardiac function has yet to be elucidated, especially in experimental diabetic animals.MethodsFor this reason, twenty diabetic mice were randomly assigned to IVBD-treated (10 mg/kg/day) and control (saline) groups. After a 3-month treatment, microarray assay was performed to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…All these functions subsequently resulted in cardiac remodeling and heart failure. In accordance with our results, animal studies also showed that MMP-2 expression and activity was increased in the diabetic heart (3,4). Therefore, we suggest that high glucose levels up-regulate the expression of MMP-2, which further promotes ECM degradation, increased HCF migration and proliferation, finally resulting in fibrosis and DCM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All these functions subsequently resulted in cardiac remodeling and heart failure. In accordance with our results, animal studies also showed that MMP-2 expression and activity was increased in the diabetic heart (3,4). Therefore, we suggest that high glucose levels up-regulate the expression of MMP-2, which further promotes ECM degradation, increased HCF migration and proliferation, finally resulting in fibrosis and DCM.…”
Section: Discussionsupporting
confidence: 90%
“…Among the MMPs, MMP-2 and MMP-9 are the major gelatinases that play an important role in the development of DCM by degrading the ECM (2). MMP-2 expression is higher in a diabetic heart (3,4). Moreover, dysregulation of MMP proteins and their endogenous inhibitor, namely, tissue inhibitor of metalloproteinase (TIMP), has been observed in the diabetic heart, suggesting that MMPs/TIMPs are involved in DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Increased cardiomyocyte apoptosis was a predominant cause of loss of contractile tissue, cardiac remodeling and, eventually, dysfunction [8]. Our previous study showed that inhibition of cardiomyocyte apoptosis improved cardiac function in diabetic mice [9]. Thus, anti-apoptosis is a potential treatment strategy for DCM.…”
Section: Introductionmentioning
confidence: 99%
“…According to our theory, this early MMP-2 downregulation is reverted during the progression of diabetic cardiomyopathy, causing an increased deposition of degraded collagen and the development of the fibrosis and apoptotic cell death. Indeed, at this late stage, the pharmacological inhibition of this process by ivabradine determines a normalization of MMP-2 activation, the prevention of apoptosis, and an improvement of cardiac dysfunction [ 44 ].…”
Section: Discussionmentioning
confidence: 99%